Utility of three dimensional (3-D) ultrasound and power Doppler in identification of high risk endometrial cancer at a tertiary care hospital in southern India: A preliminary study - Harshitha Pandey; Shyamala Guruvare; Rajagopal Kadavigere; Chythra R. Rao (Elsevier, 2018)
Objective: The study was conducted to find the utility of three dimensional (3-D) ultrasound and Doppler sonography in differentiating benign and malignant endometrial lesions and to ascertain the association of sonology parameters with type, grade and stage of endometrial cancer. Materials and methods: Women attending the gynaecology department of a tertiary care hospital, with a provisional diagnosis of carcinoma endometrium were subjected to three dimensional power Doppler ultrasound evaluation and assessment of vascular patterns. VOCAL (Virtual Organ Computer-aided Analysis) software was used to assess volume, Vascularisation Index (VI), Flow Index (FI) and Vascularisation Flow Index (VFI). Ultrasound parameters were compared with histologic diagnosis to evaluate the diagnostic performance using Receiver Operating Characteristic (ROC) Curve. Results: Sixty-four women were included in the study, 33 with benign and 31 with malignant endometrial lesions. Larger endometrial volume and higher Doppler indices correlated with malignant lesions. The variables with good discriminatory potential between benign and malignant status were VI and VFI, having a sensitivity of 90.3% and specificity of around 80%. VFI (adjusted odds ratio of 40.4; (95% CI - 8.46-192.88), p value < 0.001) was the only significant variable identified by multivariate logistic regression, when adjusted for age and post-menopausal status. Multiple global and focal vessel pattern was seen predominantly in malignant cases (specificity 93.9%), although the sensitivity was low (61.2%). Higher stages and grades of tumour and non-endometrioid types had higher Doppler indices, and requires further evaluation. Conclusions: 3-D ultrasound has good discrimination potential between benign and malignant endometrial lesions and could be useful as a screening tool. However, utility of 3-D tool for differentiation between tumour characteristics needs further validation. Keywords: Endometrial cancer, Three dimensional ultrasound, Power Doppler, Vessel patterns, Vascularisation flow index